Reducing hypnotic use in insomnia management among Australian veterans: results from repeated national interventions - Kalisch Ellett, Lisa M. (BMC Health Serv Res, 2018)
BACKGROUND: The Australian Government Department of Veterans’ Affairs (DVA) Veterans’ Medicines Advice and Therapeutics Education Services (Veterans’ MATES) programme conducted two intervention (March 2009, follow-up intervention June 2012) both of which aimed to reduce hypnotic use among Australian veterans. We evaluated the effectiveness of the interventions, and estimated the associated health consequences. METHODS: Both interventions targeted veterans who had been dispensed hypnotics prior to the intervention. Patient-specific prescriber feedback containing patient details and the volume of hypnotics dispensed, along with tailored educational information, was mailed to general practitioners. Veterans, pharmacists and directors of care in residential aged care facilities were mailed tailored educational information. Interrupted time-series and segmented regression modelling were used to determine the effect of the two interventions on the rate of hypnotics dispensing. The cumulative patient-months of hypnotic treatment avoided as a result of the interventions was calculated. We estimated improvements in health consequences of as a result of hypnotic treatment avoided based on the results of cohort studies in the same population identifying the association between hypnotic and sedative use on the outcomes of falls, and confusion. RESULTS: After the first Veterans’ MATES intervention in March 2009, hypnotic use declined by 0.2% each month, when compared to the baseline level (p = 0.006). The intervention effect was attenuated after one year, and use of hypnotics was found to increase by 0.2% per month after March 2010. Following the second intervention in June 2012, there was a further significant decline in use of 0.18% each month over the 12 months of follow up (p = 0.049). The cumulative effect of both interventions resulted in 20,850 fewer patient-months of treatment with hypnotics. This cumulative reduction in hypnotic use was estimated to lead to a minimum of 1 fewer hospital admissions for acute confusion and 7 fewer hospital admissions due to falls. CONCLUSIONS: The Veterans’ MATES insomnia interventions which involved multiple stakeholders were effective in reducing hypnotic use among older Australians. Repetition of key messages led to sustained practice change.